The Institutional and Legal Framework Of Emerging Capital Markets: The Experience Of Cis Countries - et. al., Said Gulyamov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study focuses on the development of one of the key institutions of the market economy – namely, the securities market in terms of its role in promoting competitive conditions in the financial services sector. Due to a variety of objective and subjective factors, banks have become the most dominant institutions in all CIS countries in terms of, both, accumulating and redistributing financial resources. Particularly, the research outlines the background to capital market formation and development in CIS countries through a brief history of the CIS; considers the necessity of capital market and its regulation in CIS countries; reviews the institutional and legal framework of capital market regulation, and analyzes certain problems of capital market development.